PENGARUH MODEL PEMBELAJARAN KOOPERATIF NHT TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP - Asyraful Ihsan; Hafriani; Lasmi (Mathieu : Journal of Mathematics Education and Learning, 2025)
This study aims to examine the effect of the cooperative learning model Number Head Together (NHT) on the mathematical communication skills of eighth-grade students at MTsN 4 Abdya. The research employed an experimental method with a pretest-posttest control group design. The sample, selected through random sampling, consisted of two classes: an experimental class and a control class. The research instruments included lesson plans, student worksheets, and pretest-posttest assessments of mathematical communication skills. Data were collected using mathematical communication tests. The first hypothesis test showed that = 30.78 > = 2.03, indicating a significant effect of the NHT model on students’ mathematical communication skills. The second hypothesis test yielded = 4.2 > = 1.69, meaning students taught with the NHT model demonstrated better mathematical communication skills than those taught with conventional methods. Therefore, the NHT model is proven effective in enhancing mathematical communication skills and is recommended for use in mathematics instruction.